Heterogeneous and dynamic impacts of carbon emissions on PPI and CPI: important insights into the consequences on the price system in tackling climate change - Li, Chao; Chen, Liping (Frontiers in Environmental Science, 2025)
Reducing carbon emissions is critical for addressing the challenges of climate change and represents an important step toward achieving the United Nations Sustainable Development Goals (SDGs). How to minimize disruptions to price levels within the economic system during the process of carbon reduction is an urgent issue that requires systematic investigation. In this paper, the nonlinear impact of carbon emissions on PPI (Producer Price Index) and CPI (Consumer Price Index) is deeply explored by using the Quantile-on-Quantile approach. In addition, the dynamic characteristics of this impact in the short-, middle- and long-term are systematically investigated through wavelet decomposition. It is found that, in general, there is significant heterogeneity in the impact of carbon emissions on PPI with the movement of the quantiles of the two factors. From a dynamic perspective, the impact of carbon emissions on PPI is not obvious in the short-term, shows a negative effect in the middle-term, and exhibits volatile effects in the-long term across different quantiles of PPI. In contrast, the effect of carbon emissions on CPI is relatively insignificant. However, in the middle-term and long-term, carbon emissions have negative effects on CPI within certain quantile intervals. Further analysis reveals that PPI exerts a positive impact on CPI, with this positive effect becoming more pronounced over time. These findings offer valuable insights for mitigating the disruptions caused by carbon reduction measures on production and consumer prices.